Pragmatisme Partai Dakwah dalam Pemilu 2009 - WARJIO WARJIO (Politeia: Jurnal Ilmu Politik, 2010)
Election 2009 has provided a description that pragmatism has become a hallmark of the elec-tion. One participant's election is the Partai Keadilan Sejahtera (PKS). As a party, known by the party dakwah, pragmatism shown in the Partai Keadilan Sejahtera course is very contra-dictory Partai Keadilan Sejahtera platform that is very concerned with matters relating to Is-lamic religious values. The study looks at the causes of pragmatism Partai Keadilan Sejahtera. The results showed that the main cause of the attitude of pragmatism by PKS because PKS pre-fer the politics of power politics than preaching. This path was chosen despite Partai Keadilan Sejahtera must accept the risk of abandoned although some of the founders, members, or con-stituents. This clearly shows that the Partai Keadilan Sejahtera such as no other choice than to change the political orientation. Thus the Partai Keadilan Sejahtera is more concerned with se-cular values than the values of Islam as his political views.Keywords: Islamic party, Party dakwah, General elections.